2021
DOI: 10.1042/bsr20204086
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of immune-related lncRNAs to improve the prognosis prediction for patients with papillary thyroid cancer

Abstract: Objective: To identify immune-related lncRNAs in papillary thyroid cancer (PTC). Methods: The Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases were used to obtain the gene expression profile. Immune-related long non-coding RNAs (lncRNAs) were screened from the Molecular Signatures Database v4.0 (MsigDB). We performed a survival analysis of critical lncRNAs. Further, the function of prognostic lncRNAs was inferred using the Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Of the nine autophagy-related lncRNAs, ve lncRNAs (AL136366.1, AC008063.1, AC092279.1, DOCK9-DT, LINC02471) were protective factors for the prognosis of thyroid cancer, while other four lncRNAs (LINC02454, AC096677.1, AC004918.3, AL162231.2) behaved the opposite. LINC02454 and AL136366.1 have been shown to be pivotal mediators in the pathophysiological process of PTC and are closely associated with the development and prognosis of thyroid cancer [29]. Tan et al reported that LINC02454 is highly expressed in PTC [30].…”
Section: Discussionmentioning
confidence: 99%
“…Of the nine autophagy-related lncRNAs, ve lncRNAs (AL136366.1, AC008063.1, AC092279.1, DOCK9-DT, LINC02471) were protective factors for the prognosis of thyroid cancer, while other four lncRNAs (LINC02454, AC096677.1, AC004918.3, AL162231.2) behaved the opposite. LINC02454 and AL136366.1 have been shown to be pivotal mediators in the pathophysiological process of PTC and are closely associated with the development and prognosis of thyroid cancer [29]. Tan et al reported that LINC02454 is highly expressed in PTC [30].…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA LINC00460 plays crucial roles in several epithelial cancers [60][61][62] , promoting EMT by facilitating peroxiredoxin-1 into the nucleus in HNSCC 63 . The role of LINC02454 was mainly reported in thyroid cancer [64][65][66] . Abnormal expression of LINC02454 was associated with advanced stage and poor outcome of thyroid cancer 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of LINC02454 was associated with advanced stage and poor outcome of thyroid cancer 66 . Besides, LINC02454 was deemed as an important immune-related biomarker in auxiliary prognosis prediction for patients with papillary thyroid cancer 65 . High expression of lncRNA SNHG25 promotes cell proliferation, migration and invasion, and decreased apoptosis by up-regulating COMP in epithelial ovarian cancer 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have constructed prognostic signatures of TC patients. Most research has focused on immune-related genes, like Gan et al 77 Li et al 78 Peng et al, 79 and so on. They established different immune-related signatures to predict the prognosis of patients with TC.…”
Section: Dovepressmentioning
confidence: 99%